Self-determination of the information user in times of social access to digital contents - Urbano, Cristóbal (Anuario ThinkEPI, 2018)
A reflection on the need to enhance the self-determination of the information user in relation to assisted and social information discovery systems, which often offer decontextualized information feeds. User-conscious planning and decision making in relation to the search for and use of information is the result of learning and experience, an essential input to a person´s intellectual growth. The art of asking good questions, together with the ability to discriminate the form, origin and function of recorded information, build up people´s ability to better select the answers from retrieval systems and social feeds, and this is especially important in the formative stages of a person´s education, from elementary school to university.
Keywords: Personal self-determination; Information seeking behavior; Social networks; Information literacy; Slow information.